The β-Lactamase Inhibitor Boronic Acid Derivative SM23 as a New Anti-Pseudomonas aeruginosa Biofilm - Peppoloni, Samuele; Pericolini, Eva; Colombari, Bruna; Pinetti, Diego; Cermelli, Claudio; Fini, Francesco; Prati, Fabio; Caselli, Emilia; Blasi, Elisabetta (Frontiers in Microbiology, 2020)
Pseudomonas aeruginosa is a Gram-negative nosocomial pathogen, often causative agent of severe devise-related infections, given its great capacity to form biofilm. P. aeruginosa finely regulates the expression of numerous virulence factors, including biofilm production, by Quorum Sensing (QS), a cell-to-cell communication mechanism used by many bacteria. Selective inhibition of QS-controlled pathogenicity without affecting bacterial growth may represent a novel promising strategy to overcome the well-known and widespread drug-resistance of P. aeruginosa. In this study, we investigated the effects of SM23, a boronic acid derivate specifically designed as β-lactamase inhibitor, on biofilm formation and virulence factors production by P. aeruginosa. Our results indicated that SM23: a) inhibited biofilm development and production of several virulence factors, such as pyoverdine, elastase and pyocyanin, without affecting bacterial growth; b) decreased the levels of 3-oxo-C12-HSL and C4-HSL, two QS-related autoinducer molecules, in line with a dampened lasR/lasI system; c) failed to bind to bacterial cells that had been preincubated with P. aeruginosa-conditioned medium; d) reduced both biofilm formation and pyoverdine production by P. aeruginosa onto endotracheal tubes, as assessed by a new in vitro model closely mimicking clinical settings. Taken together, our results indicate that, besides inhibiting β-lactamase, SM23 can also act as powerful inhibitor of P. aeruginosa biofilm, suggesting that it may have a potential application in the prevention and treatment of biofilm-associated P. aeruginosa infections.